Pengembangan Media Pembelajaran Monopoli Berbasis STEAM pada Mata Pelajaran IPAS untuk Melatih Kemampuan Problem Solving Peserta Didik Kelas V di SDN 1 Darmaji - Naola Salsabila; Hasnawati; Ibrahim (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This research aims to develop a STEAM-based Monopoly learning media in the science and social (IPAS) subject to train the problem-solving skills of fifth-grade students at SDN 1 Darmaji, ensuring the media is valid, practical, and effective. The method used is Research and Development (R&D) with a model consisting of Analysis, Design, Development, Implementation, and Evaluation (ADDIE). The research subjects consist of 1 teacher and 20 fifth-grade students, while the research object was the STEAM-based Monopoly learning media. Data collection instruments include observation sheets, interview guidelines, a preliminary study questionnaire, an expert validation questionnaire, a practicality questionnaire, and tests. The data collected through observation, interviews, questionnaires, and tests. Afterward, it was analyzed by qualitative and quantitative descriptively. The research results showed that the media’s validity level achieved a percentage of 81.73% from subject matter experts, included into the “highly valid” category, and 92% from media experts, also included into the “highly valid” category. The practicality level, based on teachers’ responses, was 85% in the “highly practical” category, and based on students’ responses, was 93% in the “highly practical” category. The effectiveness level indicates an N-gain score of 0.62, classified as moderate, which means the media is quite effective in developing students’ problem-solving skills. The STEAM-based Monopoly learning media has proven to be highly valid, very practical, and sufficiently effective being used in learning process of IPAS subject for fifth-grade students at SDN 1 Darmaji.